Bridging theory and practice: evaluating LIS students’ attitudes and commitment to SIWES at Federal University Oye-Ekiti - Bankole, Olubanke M.; Olusola, Ayomide O.; Momoh, Ismail A. (Communicate: Journal of Library and Information Science, 2025)
This study investigates the attitudes and commitment of Library and Information Science (LIS) undergraduates towards the Students Industrial Work Experience Scheme (SIWES) at the Federal University Oye-Ekiti, Nigeria. SIWES was established to complement theoretical knowledge with practice acquired in the industry and is also most relevant for fields such as LIS, where practice is an indispensable part of the profession. A descriptive survey approach was used to collect data from 400-level LIS students’ post-internship to assess the skills and competencies acquired, students’ attitudes and commitment to SIWES, the impact of SIWES on students’ proficiency, and challenges encountered during the SIWES Programme. The findings showed that all respondents, 135 (100.0%), acquired skills in shelf arrangement, time management, and subject classification. On attitude, most students (87.4%) resumed early at duty post, and 82.9% saw SIWES as part of their training. However, 64.5% reported absenteeism due to previous college freedom. Students’ level of commitment to SIWES was high, with a grand mean of 3.36. Relating the impact of SIWES on LIS students’ proficiency and performance, most of the respondents 132 (97.8%) agreed that SIWES exposure stimulated more interest in the workroom and practical activities, followed by 127 (94.1%) respondents who agreed that their performance on practicals improved after SIWES exposure. Students faced significant challenges such as placement difficulty, delayed resources, a poor orientation programme, and a need for SIWES incentives. The study recommends continued supervisory support by University and industry-based supervisors to improve the attitude and commitment of FUOYE LIS students and preparatory programmes to enhance SIWES efficacy and students’ preparedness for professional roles.